Do college admissions criteria matter? Evidence from discretionary vs. grade-based admission policies. (February 2023) - Kamis, Rais; Pan, Jessica; Seah, Kelvin KC
Highlights: We examine the implications of college admissions criteria on students' outcomes. Examine admissions at a large university with two admission tracks. Regular admission track is based exclusively on academic performance while discretionary track considers non-academic qualities. Discretionary admission students enjoy significantly higher earnings compared to marginal group of regular admission students. Earnings advantage persists up to three years after graduation. Abstract: This paper examines the implications of college admissions criteria on students' academic and non-academic performance in university and their labor market outcomes. We exploit a unique feature of the admissions system at a large university in Singapore, the National University of Singapore, that has two admission tracks – a regular admission track where admission is based exclusively on academic performance and a discretionary admission (DA) track where applicants can instead gain admission on the basis of demonstrated non-academic qualities. Comparing students admitted through each track, we find that DA students fare similarly in terms of academic performance in university as marginal students admitted through the regular route. However, they are significantly more likely to be involved in optional academic and non-academic college activities and earn substantially higher labor market earnings up to three years after graduation. These results are not driven by the DA process differentially selecting students on the basis of family background or unobserved academic ability.